The Impact Of Islamic Financial Development On Malaysian Economic Growth - Musa, Gani Ibrahim (2020)
The protagonist of financial development in influencing economic growth through capital accumulation and productivity of capital has been the central issue in the economic growth literature. The interest-based conventional financial development provided several empirical shreds of evidence on this issue. However, the emergence and success of Islamic finance is a great achievement in a global financial development. Can Islamic financial development be able to influence economic growth? Therefore, this study aims to investigate the impact of Islamic financial development on Malaysian economic growth. Malaysia is the leading country in term of Islamic financial activities (NST 2018). This study examined Islamic banking and capital market development as the measures of Islamic financial development (IFD) on economic growth, through capital accumulation and productivity of capital, over the period from 1998 to 2018. It also determined the causal relationship between IFD and Malaysian economic growth. The study adopted time series co-integration techniques, which involve autoregressive distributive lag (ARDL) by Pesaran, Shin and Smith (2001), to determine the long-run and short-run relationship between IFD and economic growth. It further employed Granger vector error correction model (VECM) to determine the causal relationship between IFD indicators and economic growth in Malaysia. The findings show that Islamic banking and capital market development has a positive and significant relationship with economic growth in the long-run.